Changing paradigms in the management of forest insect disturbances. (15th December 2016) - Alfaro, René I.; Langor, David
Abstract: From the early descriptive work, focussed on documenting the forest insect fauna and the impacts of destructive species, Canadian forest entomology has passed through several distinct phases, each triggered by new societal demands of forests and of forest entomologists. We review the various stages that Canadian forest entomology gone through in the last 100 years. Following the initial descriptive and cataloguing phase, forest entomology entered a pest control or forest protection phase, which eventually evolved into the integrated pest management (IPM) era. Although IPM dominated the forest entomology discourse for at least two decades, this approach is now considered to be narrow and pest-centric and is being superseded by a more holistic approach where the emphasis is on ensuring the health and sustainability of forests at landscape levels. The new trends point away from the "command and control" approach of attempting to eradicate pests or reducing pest damage, and towards working with natural processes in the context of ecosystem management. We indicate several areas where 21st century forest entomology could make a contribution towards the sustainable management of Canadian forests.